Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Phyto-inspired cyclic peptides derived from plant Pin-II type protease inhibitor reactive center loops for crop protection from insect pests - Sailthedkar, Nidhi S.; Joshi, Rakesh S.; Yadav, Amit K.; Seal, Shubhendu; Fernandes, Moneesha; Giri, Ashok P. (Biochimica ET Biophysica Acta-General Subjects, 2019)
Background: Natural defence of plants against insect pests involves protease inhibitors (PIs) that interfere with insect digestive proteases. Pin-II type plant PIs are wound inducible upon insect damage and possess multiple inhibitory repeat domains that can inhibit trypsin and chymotrypsin-like proteases in the insect midgut. Yet, their agricultural ex-vivo application is limited due to large molecular size and environmental instability, which could be overcome by small peptides. Methods: Bicyclic peptides were designed by grafting Pin-II PIs derived reactive center loop (RCL) on synthetic tris(bromomethyl)benzene scaffold. In vitro binding with trypsin-like proteases was evaluated by biochemical and biophysical assays, followed by molecular dynamics simulations. In vivo effects on two major lepidopteran insect pests, Helicoverpa armigera and Spodoptera litura were studied upon feeding with peptide treated leaves. Affinity based pull down assays were used to identify target proteins in insect gut. Results: Bicyclic RCLs showed ten-fold enhanced protease inhibition compared to their linear counterparts. They exhibited feeding deterrence and growth reduction of lepidopteran insects. Bicyclic peptides predominantly interact with midgut serine proteases. Possible binding modes involve simultaneous interaction with the active site and specificity-determining residues of insect gut trypsin. Conclusion: Bicyclic peptides are potent inhibitors of serine proteases in the insect midgut. They cause feeding aversion and larval growth retardation. Bi-domain cyclic peptides interact with two sites on trypsin, leading to enhanced efficacy over linear RCL peptides. General significance: Bicyclic peptides mimic natural PIs by inhibiting insect proteases leading to growth reduction, thus, could be used as pest control molecules in agriculture.
Keywords: Cyclic peptide; Lepidoptera; Pest control; protease inhibitor; Reactive loop

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes